The Illustrated encyclopedia of the animal kingdom - Knauth, Percy, 1914 (New York : Danbury Press, 1972)
Discusses the development and characteristics of a wide variety of the world's animals
"Translated and adapted from Gli Animali e il loro mondo."
1
Keywords: Animals; Zoology; Animals; Zoology